Preparation method and application of full-particle-size steel slag gradient carbonization artificial aggregate suitable for asphalt ultrathin wearing layer
Through the preparation method of the full-particle steel slag gradient carbonized artificial aggregate, the problem of slowing down the reaction rate of steel slag carbonization in the prior art and insufficient utilization of multiple solid waste resources is solved, the high strength and stability of carbonized steel slag is achieved, and the resource utilization rate is improved.
Patent Information
- Application Number
- CN202411941080.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The existing steel slag carbonization methods have led to a slowdown in the late stage of carbonization, which has limited the improvement of the degree of carbonization of the core part of the steel slag, and has not fully utilized the comprehensive utilization of diversified solid waste resources.
The preparation method of full-particle steel slag gradient carbonized artificial aggregate is adopted. Through crushing, magnetic separation, screening, high-pressure water erosion, drying, pre-curing, granulation and pre-curing, the uniform carbonization of steel slags of different particle sizes is ensured, and substances such as biochar, fly ash and ammonium carbonate are added during the granulation process.
It significantly improves the stability and strength of artificial aggregates of carbonized steel slag, improves the resource utilization rate of waste, and achieves the coordinated stimulation effect of diversified solid waste such as steel slag, biochar, fly ash.
Smart Images

Figure CN119707337A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of artificial aggregate, and belongs to the technical field of solid waste utilization and road paving materials. Background Art
[0002] Steel slag is an industrial waste produced during the steelmaking process in my country. It has the characteristics of high strength, wear resistance, and anti-skid, and has been used in asphalt pavements. However, the bottleneck that limits the widespread application of steel slag in asphalt pavements is that the steel slag contains a large amount of free calcium oxide and other substances with high carbonization activity. These substances are prone to volume expansion when reacting with water, which in turn causes cracking and other defects in asphalt concrete. At the same time, a large amount of natural high-quality aggregates are easily consumed during highway construction, resulting in an increasing demand for natural aggregate substitution. Fully carbonizing steel slag is an important means to solve the problems of carbon dioxide sequestration, natural aggregate substitution, and efficient utilization of steel slag resources.
[0003] In the existing steel slag carbonization method, during the steel slag carbonization process, as the carbonization product calcium carbonate increases, the carbonization product forms a dense carbonization layer on the steel slag surface, which hinders the further diffusion of carbon dioxide and ions, resulting in a slowdown in the reaction rate of the steel slag carbonization in the later stage, limiting the improvement of the carbonization degree of the core part of the steel slag, resulting in poor strength of the carbonized steel slag. At the same time, only using a single steel slag solid waste is not conducive to the comprehensive resource utilization of multiple solid wastes such as fly ash and biochar. Summary of the invention
[0004] The present invention aims to solve the technical problems of low strength of existing carbonized steel slag aggregate and inability to give full play to the comprehensive utilization of multiple solid waste resources, and to provide a preparation method and application of full-size steel slag gradient carbonized artificial aggregate suitable for ultra-thin asphalt wear layer.
[0005] The method for preparing the full-size steel slag gradient carbonized artificial aggregate suitable for the ultra-thin asphalt wearing layer of the present invention is carried out according to the following steps:
[0006] 1. The steel slag is crushed, magnetically separated and sieved in sequence to obtain steel slag with a particle size d in the following 8 sizes, namely, d<0.075mm, 0.075≤d<0.15mm, 0.15≤d<0.3mm, 0.3≤d<0.6mm, 0.6≤d<1.18mm, 1.18≤d<2.36mm, 2.36≤d<4.75mm, 4.75≤d<9.5mm;
[0007] Use high-pressure water to flush the surface of steel slag with 6 particle sizes, namely 0.15≤d<0.3mm, 0.3≤d<0.6mm, 0.6≤d<1.18mm, 1.18≤d<2.36mm, 2.36≤d<4.75mm, and 4.75≤d<9.5mm, to remove dust and impurity layers attached to the surface of the steel slag;
[0008] Subsequently, steel slag aggregates of 8 particle sizes, namely, d<0.075mm, 0.075≤d<0.15mm, 0.15≤d<0.3mm, 0.3≤d<0.6mm, 0.6≤d<1.18mm, 1.18≤d<2.36mm, 2.36≤d<4.75mm, and 4.75≤d<9.5mm, were placed in an oven at 130-150°C for heating and drying for 8-12h;
[0009] 2. Placing the steel slag aggregates of the eight particle sizes treated in step 1 in a curing box isolated from a carbon dioxide environment for steel slag pre-curing treatment, spraying deionized water mist on the steel slag of each particle size, and stirring, so that the steel slag undergoes a sufficient hydration reaction before carbonization; wherein, the amount of deionized water sprayed into the steel slag of 4.75≤d<9.5mm is 15% to 20% of the mass of the steel slag, and the amount of deionized water sprayed increases by 0.5% for each particle size reduction;
[0010] 3. Granulation and curing treatment of steel slag with eight particle sizes were carried out respectively under normal temperature and pressure: first, steel slag aggregates of any particle size, biochar powder, fly ash powder and ammonium carbonate powder were placed in a disc granulating device, and the granulating device was rotated for 5 to 10 minutes under the conditions of an inclination angle of 45° and a stirring speed of 15 to 20 r / min for granulation treatment. During the whole granulation process, water mist formed by deionized water and sodium bicarbonate was sprayed on the mixture in the disc device, and carbon dioxide gas with a volume percentage concentration of 85% to 95% was applied at the same time, thereby obtaining carbonized steel slag artificial aggregate with a higher particle size;
[0011] Among them, when the steel slag with a size of d < 0.075 mm is subjected to granulation and curing treatment to prepare the steel slag aggregate with a size of 0.075 ≤ d < 0.15 mm, the mass of the biochar powder, fly ash powder and ammonium carbonate powder is 3% to 10% of the mass of the steel slag, and the mass of the sodium bicarbonate is 3.5% to 5.0% of the mass of the steel slag; when the particle size of the steel slag is increased by one level, the mass of the biochar powder, fly ash powder and ammonium carbonate powder is increased by 0.5%, and the mass of the sodium bicarbonate is increased by 0.3%;
[0012] 4. Pre-curing the carbonized steel slag artificial aggregate: pre-curing the carbonized steel slag artificial aggregate of different particle sizes obtained in step 3 under normal pressure, temperature 25° C., and relative humidity 60% to 70% to give the carbonized steel slag artificial aggregate an initial strength;
[0013] Among them, the pre-curing time of the artificial aggregate of carbonized steel slag with a particle size of 9.5≤d<13.2mm is 15-18h; the pre-curing time increases by 3h for each decrease in the particle size of the artificial aggregate of carbonized steel slag;
[0014] 5. Post-curing the above-mentioned carbonized steel slag artificial aggregate: placing the carbonized steel slag artificial aggregate of different particle sizes after pre-curing treatment in a supercritical carbon dioxide reactor, introducing carbon dioxide gas for carbonization at a pressure of 8-10 MPa, a temperature of 40-60° C., and a relative humidity of 60%-70%; wherein the carbon dioxide concentration is 95%-100%, and the carbon dioxide gas flow rate is 5-15 L / min; during the post-curing treatment of the carbonized steel slag artificial aggregate of each particle size, turning the carbonized steel slag artificial aggregate several times (4-6 times) to achieve uniform carbonization;
[0015] Among them, the post-curing time of the artificial aggregate of carbonized steel slag with a particle size of 9.5≤d<13.2mm is 15-20min; the pre-curing time increases by 3min for each decrease in the particle size of the artificial aggregate of carbonized steel slag;
[0016] After the post-curing treatment is completed, full-size steel slag gradient carbonized artificial aggregate suitable for asphalt ultra-thin wearing layer is obtained.
[0017] Furthermore, the steel slag in step 1 is any one or more of converter slag, electric furnace slag, and ladle refining slag.
[0018] The method for preparing an asphalt mixture of an ultra-thin asphalt wearing layer by using full-size steel slag gradient carbonized artificial aggregate is carried out in the following steps:
[0019] First, the full-size steel slag gradient carbonized artificial aggregate is crushed and screened to obtain the carbonized steel slag artificial aggregate with a particle size d in the following 8 particle size ranges, namely, d<0.075mm, 0.075≤d<0.15mm, 0.15≤d<0.3mm, 0.3≤d<0.6mm, 0.6≤d<1.18mm, 1.18≤d<2.36mm, 2.36≤d<4.75mm, 4.75≤d<9.5mm; the purpose is to make the carbonized steel slag artificial aggregate with different particle size ranges have irregular shapes, which are more in line with the shape of natural aggregates;
[0020] 2. Use carbonized steel slag artificial aggregate as the coarse and fine aggregate of the asphalt mixture, use a mixture of carbonized steel slag powder with the same particle size as basalt mineral powder and basalt mineral powder in a volume ratio of 1:1 as the filler of the asphalt mixture, add asphalt and fiber, and prepare an ultra-thin wearing layer asphalt mixture.
[0021] Furthermore, the mass of asphalt in the asphalt mixture is 4-6% of the mass of the asphalt mixture.
[0022] Furthermore, the fibers in the asphalt mixture are steel slag fibers, and the mass of the steel slag fibers is 0.2-0.4% of the mass of the asphalt mixture.
[0023] Furthermore, the gradation of the ultra-thin wearing layer asphalt mixture is SMA-10, OGFC-10 or AC-10 asphalt mixture.
[0024] The present invention performs crushing-curing-synthesis treatment on steel slag of all particle sizes, especially adds biochar, fly ash and ammonium carbonate and other substances in the granulation curing process, and adopts different carbonization process parameters for steel slags of different particle sizes, so as to fully guarantee the carbonization quality of steel slags of different particle sizes, realize the uniform carbonization of the outside and inside of steel slags of different particle sizes, improve the performance of steel slag, and increase the resource utilization rate of waste; at the same time, as the carbonization process of steel slag proceeds, carbonization can reduce the carbonization activity of the substances inside the steel slag and increase the hydration activity, while the carbonization activity of the substances inside the steel slag is reduced. The reduction of can alleviate the risk of slag volume instability, and the increase of hydration activity can promote the formation of cementitious products, thereby improving the strength of carbonized slag. Therefore, the present invention realizes the coordinated balance design of slag carbonization and hydration activity in the slag carbonization process, and significantly improves the stability and strength of carbonized slag artificial aggregate; in addition, spraying deionized water mist in the pre-curing stage and performing preliminary strength curing in the pre-curing stage also realizes the coordinated balance design of carbonization and hydration activity of slags with different particle sizes, further promoting the stability and strength of carbonized slag artificial aggregate.
[0025] The full-size steel slag gradient carbonized artificial aggregate suitable for ultra-thin asphalt wear layer prepared by the present invention has an average carbon fixation of 12.4%, an average free calcium oxide content of 0.32%, and an average compressive strength of 54.32MPa; the volume expansion rate of the artificial aggregate when kept at a temperature of 60°C for 5 days is 0.32%. The ultra-thin wear layer SMA-10 type asphalt mixture is prepared using the full-size steel slag gradient carbonized artificial aggregate, and its dynamic stability is 13285 times / mm, the immersion Marshall is 96.5%; the anti-skid performance BPN value is 0.76. The present invention gives full play to the role of solid waste materials such as biochar and fly ash in improving the carbonization degree of steel slag, realizes the preparation of carbonized steel slag artificial aggregate synergistically stimulated by multiple solid wastes such as steel slag, biochar, and fly ash, and improves the efficient resource utilization rate of different types of bulk solid wastes. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The present invention is a schematic diagram of the preparation process of full-size steel slag gradient carbonized artificial aggregate suitable for ultra-thin asphalt wearing layer. DETAILED DESCRIPTION
[0027] The beneficial effects of the present invention are verified by the following examples.
[0028] Embodiment 1: The preparation method of the full-size steel slag gradient carbonized artificial aggregate suitable for the ultra-thin asphalt wearing layer of this embodiment is carried out according to the following steps:
[0029] 1. Crushing, magnetic separation and screening the steel slag in sequence to obtain steel slag aggregates with a particle size d in the following 8 sizes, namely, d<0.075mm, 0.075≤d<0.15mm, 0.15≤d<0.3mm, 0.3≤d<0.6mm, 0.6≤d<1.18mm, 1.18≤d<2.36mm, 2.36≤d<4.75mm, 4.75≤d<9.5mm;
[0030] Use high-pressure water to flush the surface of steel slag with 6 particle sizes, namely 0.15≤d<0.3mm, 0.3≤d<0.6mm, 0.6≤d<1.18mm, 1.18≤d<2.36mm, 2.36≤d<4.75mm, and 4.75≤d<9.5mm, to remove dust and impurity layers attached to the surface of the steel slag;
[0031] Subsequently, steel slag aggregates of 8 particle sizes, namely, d<0.075mm, 0.075≤d<0.15mm, 0.15≤d<0.3mm, 0.3≤d<0.6mm, 0.6≤d<1.18mm, 1.18≤d<2.36mm, 2.36≤d<4.75mm, and 4.75≤d<9.5mm, were placed in an oven at 135℃ and heated and dried for 12h;
[0032] 2. The steel slag aggregates of 8 particle sizes treated in step 1 are placed in a curing box isolated from a carbon dioxide environment for steel slag pre-curing treatment, and deionized water mist is sprayed on the steel slag of each particle size and stirred to allow the steel slag to undergo a sufficient hydration reaction before carbonization; the amount of deionized water sprayed into the steel slag aggregates of each particle size is shown in Table 1;
[0033] Table 1 The amount of deionized water injected into the slag of different particle sizes
[0034] Particle size The injection amount of deionized water is the percentage of slag mass d<0.075mm 21.5% 0.075≤d<0.15mm 21% 0.15≤d<0.3mm 20.5% 0.3≤d<0.6mm 20% 0.6≤d<1.18mm 19.5% 1.18≤d<2.36mm 19% 2.36≤d<4.75mm 18.5% 4.75≤d<9.5mm 18%
[0035] 3. Granulation and curing treatment of steel slag of 8 particle sizes were carried out respectively under normal temperature and pressure environment: first, steel slag aggregate of any particle size, biochar powder, fly ash powder and ammonium carbonate powder were placed in a disc granulation device, and the granulation device was rotated for 10 minutes under the conditions of an inclination angle of 45° and a stirring speed of 20r / min for granulation treatment. During the whole granulation process, a water mist formed by a mixed solution of deionized water and sodium bicarbonate was sprayed on the mixture in the disc device, and carbon dioxide with a volume percentage concentration of 90% was applied at the same time to obtain carbonized steel slag artificial aggregate with a higher particle size; wherein, the mass percentage of biochar powder, fly ash powder and ammonium carbonate powder in steel slag of each particle size to the mass percentage of steel slag is shown in Table 2;
[0036] Among them, when the steel slag with d<0.075mm is granulated and cured to prepare the steel slag aggregate with 0.075≤d<0.15mm, the mass of biochar powder, fly ash powder and ammonium carbonate powder is 6% of the mass of steel slag, and the mass of sodium bicarbonate is 4.0% of the mass of steel slag; for each increase in the particle size of steel slag, the mass of biochar powder, fly ash powder and ammonium carbonate powder increases by 0.5%, and the mass of sodium bicarbonate increases by 0.3%; the specific quantities are shown in Table 2.
[0037] Table 2 The mass percentage of each substance added during the granulation and curing of steel slag of each particle size
[0038]
[0039] 4. Pre-curing the carbonized steel slag artificial aggregate: The carbonized steel slag artificial aggregate of different particle sizes obtained above is placed in an environment of normal pressure, temperature 25°C, and relative humidity 65% for pre-curing treatment, so that the carbonized steel slag artificial aggregate has initial strength; wherein, the pre-curing time of the carbonized steel slag artificial aggregate with a particle size of 9.5≤d<13.2mm is 16h; the pre-curing time increases by 3h for each decrease in the particle size of the carbonized steel slag artificial aggregate; the pre-curing time of the carbonized steel slag artificial particles of each particle size is shown in Table 3.
[0040] Table 3 Pre-curing time of carbonized steel slag artificial particles of different particle sizes
[0041]
[0042]
[0043] 5. Post-curing treatment of the carbonized steel slag artificial aggregate treated in step 4: placing the carbonized steel slag artificial aggregate after pre-curing treatment in a supercritical carbon dioxide reactor, introducing carbon dioxide gas for carbonization at a pressure of 10MPa, a temperature of 50°C, and a relative humidity of 65%; wherein the carbon dioxide concentration is 95% and the carbon dioxide gas flow rate is 15L / min; turning the carbonized steel slag artificial aggregate 4 times during the post-curing treatment of the carbonized steel slag artificial aggregate of each particle size grade to achieve uniform carbonization; wherein, the post-curing time of the carbonized steel slag artificial aggregate with a particle size of 9.5 to 13.2 mm is 18 minutes; the pre-curing time increases by 3 minutes for each particle size reduction of the carbonized steel slag artificial aggregate; the post-curing time of the carbonized steel slag artificial aggregate of each particle size grade is shown in Table 4; after the post-curing treatment is completed, a full-size steel slag gradient carbonized artificial aggregate suitable for an ultra-thin asphalt wear layer is obtained.
[0044] Table 4 Post-solidification time of carbonized steel slag artificial particles of different particle sizes
[0045] Particle size Post-curing time (min) 0.075≤d<0.15mm 39 0.15≤d<0.3mm 36 0.3≤d<0.6mm 33 0.6≤d<1.18mm 30 1.18≤d<2.36mm 27 2.36≤d<4.75mm 24 4.75≤d<9.5mm 21 9.5≤d<13.2mm 18
[0046] Comparative Example 1: The pretreatment method of the carbonized steel slag in this comparative example is consistent with that in Example 1, but the carbonization method is different, that is, the comparative carbonized steel slag has no pre-curing process, and the process parameters of the carbonized steel slags of different particle size grades are consistent, and the carbonization process parameters of the comparative carbonized steel slags of different particle size grades are mainly based on the carbonization parameters of the 2.36≤d<4.75mm particle size grade of the carbonized steel slag artificial aggregate in the embodiment. The preparation method of the carbonized steel slag artificial aggregate in this comparative example is specifically carried out in the following steps:
[0047] 1. The steel slag is crushed, magnetically separated and sieved in sequence to obtain steel slag with a particle size d in the following 8 sizes, namely, d<0.075mm, 0.075≤d<0.15mm, 0.15≤d<0.3mm, 0.3≤d<0.6mm, 0.6≤d<1.18mm, 1.18≤d<2.36mm, 2.36≤d<4.75mm, 4.75≤d<9.5mm;
[0048] Use high-pressure water to flush the surface of steel slag with 6 particle sizes, namely 0.15≤d<0.3mm, 0.3≤d<0.6mm, 0.6≤d<1.18mm, 1.18≤d<2.36mm, 2.36≤d<4.75mm, and 4.75≤d<9.5mm, to remove dust and impurity layers attached to the surface of the steel slag;
[0049] Subsequently, steel slag aggregates of 8 particle sizes, namely, d<0.075mm, 0.075≤d<0.15mm, 0.15≤d<0.3mm, 0.3≤d<0.6mm, 0.6≤d<1.18mm, 1.18≤d<2.36mm, 2.36≤d<4.75mm, and 4.75≤d<9.5mm, were placed in an oven at 135℃ and heated and dried for 12h;
[0050] 2. Granulation and curing treatment were carried out on steel slags of eight particle sizes under normal temperature and pressure: first, steel slag aggregates of any particle size, biochar powder, fly ash powder and ammonium carbonate powder were put into a disc granulating device, and the granulating device was rotated for 10 minutes under the conditions of an inclination angle of 45° and a stirring speed of 20r / min for granulation treatment. During the whole granulation process, water mist formed by a mixed solution of deionized water and sodium bicarbonate was sprayed on the mixture in the disc device, and carbon dioxide with a volume percentage concentration of 90% was applied at the same time to obtain carbonized steel slag artificial aggregate with a higher particle size. Among them, during the granulation and curing process of steel slag aggregates of different particle sizes, the mass of biochar powder, fly ash powder and ammonium carbonate powder was 9% of the mass of steel slag, and the mass of sodium bicarbonate was 5.8% of the mass of steel slag.
[0051] 3. Pre-curing the artificial aggregate of carbonized steel slag: pre-curing the artificial aggregate of carbonized steel slag of all particle sizes for 22 hours at normal pressure, temperature 25°C, and relative humidity 65%, so that the artificial particles of carbonized steel slag have initial strength;
[0052] 4. Post-curing treatment is performed on the above-mentioned carbonized steel slag artificial aggregate: the carbonized steel slag artificial aggregate of all particle sizes after pre-curing treatment is placed in a supercritical carbon dioxide reactor, and carbon dioxide gas is introduced at a pressure of 10 MPa, a temperature of 50°C, and a relative humidity of 65% for carbonization for 24 minutes; wherein the carbon dioxide concentration is 95%, and the carbon dioxide gas flow rate is 15 L / min; during the post-curing treatment of the carbonized steel slag artificial aggregate of each particle size, the carbonized steel slag artificial aggregate is turned over 4 times to achieve uniform carbonization, thereby obtaining steel slag carbonized artificial aggregate for comparison.
[0053] The full-size steel slag gradient carbonized artificial aggregate suitable for asphalt ultra-thin wear layer prepared in Example 1 was compared with the carbonized steel slag artificial aggregate prepared in the comparative example in terms of average carbon fixation, average free calcium oxide content, average compressive strength and average volume expansion rate. The results are as follows:
[0054] The average carbon fixation of the carbonized steel slag artificial aggregate is 3.2%; the average free calcium oxide content is 0.77%; the average compressive strength is 42.71MPa; and the volume expansion rate is 0.75% when kept at 60°C for 5 days.
[0055] The average carbon fixation content of the full-size steel slag gradient carbonized artificial aggregate suitable for the ultra-thin asphalt wear layer prepared in Example 1 is 12.4%, which is 3.9 times that of the comparative carbonized steel slag artificial aggregate; the average free calcium oxide content is 0.32%, which is only 41.6% of the comparative carbonized steel slag artificial aggregate; the average compressive strength is 54.32 MPa, which is 1.3 times that of the comparative carbonized steel slag artificial aggregate; the volume expansion rate when maintained at 60°C for 5 days is 0.32%, which is only 42.7% of the comparative carbonized steel slag artificial aggregate.
[0056] It can be seen that the carbonized steel slag artificial aggregate prepared in Example 1 has a high carbon fixation content, a low free calcium oxide content, a high average compressive strength, and a small volume expansion rate, which shows that the carbonized steel slag preparation method of Example 1 can significantly promote the carbonization degree of steel slag and improve its carbonization volume stability and strength.
[0057] Example 2: Asphalt mixture is prepared using the full-size steel slag gradient carbonized artificial aggregate prepared in Example 1. The specific method is carried out according to the following steps:
[0058] 1. The full-size steel slag gradient carbonized artificial aggregate prepared in Example 1 is crushed and sieved to obtain carbonized steel slag artificial aggregate with a particle size d in the following 8 particle size ranges, namely, d<0.075mm, 0.075≤d<0.15mm, 0.15≤d<0.3mm, 0.3≤d<0.6mm, 0.6≤d<1.18mm, 1.18≤d<2.36mm, 2.36≤d<4.75mm, 4.75≤d<9.5mm; the purpose is to make the carbonized steel slag artificial aggregate of different particle size ranges have irregular shapes, which are more in line with the shape of natural aggregates;
[0059] Second, according to the mineral gradation of SMA-10 asphalt mixture, the carbonized steel slag artificial aggregate prepared in step 1 is used as the coarse and fine aggregate of SMA-10 asphalt mixture, and the mixture of carbonized steel slag powder with the same particle size as basalt mineral powder and basalt mineral powder in a volume ratio of 1:1 is used as the filler of SMA-10 asphalt mixture, and asphalt and fiber are added to prepare an ultra-thin wear layer SMA-10 asphalt mixture; wherein the mass of asphalt is 5.5% of the asphalt mixture, the fiber is steel slag fiber, and the mass of steel slag fiber is 0.3% of the asphalt mixture, and an SMA-10 asphalt mixture containing full-size steel slag gradient carbonized artificial aggregate is obtained. The gradation composition of SMA-10 asphalt mixture is shown in Table 5.
[0060] Table 5 SMA-10 asphalt mixture gradation composition
[0061]
[0062] Comparative Example 2: SMA-10 asphalt mixture is prepared with the carbonized steel slag artificial aggregate prepared in Comparative Example 1: According to the mineral grading of SMA-10 asphalt mixture shown in Table 5, the carbonized steel slag artificial aggregate prepared in Comparative Example 1 is used as the coarse and fine aggregate of the SMA-10 asphalt mixture, basalt mineral powder is used as the filler of the SMA-10 asphalt mixture, asphalt and fiber are added to prepare an ultra-thin wear layer SMA-10 asphalt mixture; wherein the mass of the asphalt is 5.5% of the asphalt mixture, the fiber is steel slag fiber, and the mass of the steel slag fiber is 0.3% of the asphalt mixture, to obtain an SMA-10 asphalt mixture for comparison.
[0063] The high temperature stability, water damage resistance and anti-skid performance of the two asphalt mixtures were tested, and the results are as follows:
[0064] The dynamic stability of the SMA-10 asphalt mixture is 10572 times / mm; the water Marshall is 91.3%; and the anti-skid performance BPN value is 0.64.
[0065] The dynamic stability of the SMA-10 asphalt mixture prepared by Example 2 is 13285 times / mm, which is 25.7% higher than that of the comparative SMA-13 asphalt mixture; the immersion Marshall is 96.5%; the anti-skid performance BPN value is 0.76, which is 18.8% higher than that of the comparative SMA-13 asphalt mixture.
[0066] It can be seen that the SMA-10 asphalt mixture prepared using the full-size steel slag gradient carbonized artificial aggregate prepared in Example 1 has good high-temperature stability, water damage resistance and anti-skid performance, which shows that the carbonized steel slag preparation method of the present invention can significantly improve the road performance of ultra-thin wearing layer asphalt mixture.
Claims
1. A method for preparing full-size steel slag gradient carbonized artificial aggregate suitable for ultra-thin asphalt wearing layer, characterized in that: The method proceeds as follows:
1. The steel slag is crushed, magnetically separated and sieved in sequence to obtain steel slag with a particle size d in the following 8 sizes, namely, d<0.075mm, 0.075≤d<0.15mm, 0.15≤d<0.3mm, 0.3≤d<0.6mm, 0.6≤d<1.18mm, 1.18≤d<2.36mm, 2.36≤d<4.75mm, 4.75≤d<9.5mm; Use high-pressure water to flush the surface of steel slag with 6 particle sizes, namely 0.15≤d<0.3mm, 0.3≤d<0.6mm, 0.6≤d<1.18mm, 1.18≤d<2.36mm, 2.36≤d<4.75mm, and 4.75≤d<9.5mm, to remove dust and impurity layers attached to the surface of the steel slag; Subsequently, steel slag aggregates of 8 particle sizes, namely, d<0.075mm, 0.075≤d<0.15mm, 0.15≤d<0.3mm, 0.3≤d<0.6mm, 0.6≤d<1.18mm, 1.18≤d<2.36mm, 2.36≤d<4.75mm, and 4.75≤d<9.5mm, were placed in an oven at 130-150°C for heating and drying for 8-12h; 2. Placing the steel slag aggregates of the eight particle sizes treated in step 1 in a curing box isolated from a carbon dioxide environment for steel slag pre-curing treatment, spraying deionized water mist on the steel slag of each particle size, and stirring, so that the steel slag undergoes a sufficient hydration reaction before carbonization; wherein, the amount of deionized water sprayed into the steel slag of 4.75≤d<9.5mm is 15% to 20% of the mass of the steel slag, and the amount of deionized water sprayed increases by 0.5% for each particle size reduction; 3. Granulation and curing treatment of steel slag with eight particle sizes were carried out respectively under normal temperature and pressure: first, steel slag aggregates of any particle size, biochar powder, fly ash powder and ammonium carbonate powder were placed in a disc granulating device, and the granulating device was rotated for 5 to 10 minutes under the conditions of an inclination angle of 45° and a stirring speed of 15 to 20 r / min for granulation treatment. During the whole granulation process, water mist formed by deionized water and sodium bicarbonate was sprayed on the mixture in the disc device, and carbon dioxide gas with a volume percentage concentration of 85% to 95% was applied at the same time, thereby obtaining carbonized steel slag artificial aggregate with a higher particle size; Wherein, when the steel slag with d<0.075mm is subjected to granulation and curing treatment to prepare the steel slag aggregate with 0.075≤d<0.15mm, the mass of biochar powder, fly ash powder and ammonium carbonate powder is 3% to 10% of the mass of the steel slag, and the mass of sodium bicarbonate is 3.5% to 5.0% of the mass of the steel slag; for each increase in the particle size of the steel slag, the mass of the biochar powder, fly ash powder and ammonium carbonate powder increases by 0.5%, and the mass of the sodium bicarbonate increases by 0.3%; 4. Pre-curing the carbonized steel slag artificial aggregate: placing the carbonized steel slag artificial aggregate of different particle sizes obtained in step 3 in an environment of normal pressure, temperature of 25° C., and relative humidity of 60% to 70% for pre-curing treatment, so that the carbonized steel slag artificial aggregate has initial strength; Among them, the pre-curing time of the artificial aggregate of carbonized steel slag with a particle size of 9.5≤d<13.2mm is 15-18h; the pre-curing time increases by 3h for each decrease in the particle size of the artificial aggregate of carbonized steel slag; 5. Post-curing the carbonized steel slag artificial aggregate obtained in step 4: placing the carbonized steel slag artificial aggregate of different particle sizes after pre-curing treatment in a supercritical carbon dioxide reactor, introducing carbon dioxide gas at a pressure of 8-10 MPa, a temperature of 40-60° C., and a relative humidity of 60%-70% for carbonization treatment; wherein the carbon dioxide concentration is 95%-100%, and the carbon dioxide gas flow rate is 5-15 L / min; during the post-curing treatment of the carbonized steel slag artificial aggregate of each particle size, turning the carbonized steel slag artificial aggregate 4-6 times to achieve uniform carbonization; Among them, the post-curing time of the artificial aggregate of carbonized steel slag with a particle size of 9.5≤d<13.2mm is 15-20min; the post-curing time increases by 3min for each decrease in the particle size of the artificial aggregate of carbonized steel slag; After the post-curing treatment is completed, full-size steel slag gradient carbonized artificial aggregate suitable for asphalt ultra-thin wearing layer is obtained.
2. The method for preparing full-size steel slag gradient carbonized artificial aggregate suitable for ultra-thin asphalt wearing layer according to claim 1, characterized in that: The steel slag described in step 1 is any one or more of converter slag, electric furnace slag, and ladle refining slag.
3. A method for preparing an asphalt mixture with an ultra-thin asphalt wearing layer using the full-size steel slag gradient carbonized artificial aggregate prepared by the method of claim 1, characterized in that: The method proceeds as follows: First, the full-size steel slag gradient carbonized artificial aggregate is crushed and screened to obtain the carbonized steel slag artificial aggregate with a particle size d in the following 8 particle size ranges, namely, d<0.075mm, 0.075≤d<0.15mm, 0.15≤d<0.3mm, 0.3≤d<0.6mm, 0.6≤d<1.18mm, 1.18≤d<2.36mm, 2.36≤d<4.75mm, 4.75≤d<9.5mm, the purpose of which is to make the carbonized steel slag artificial aggregate with different particle size ranges present irregular shapes, which are more in line with the shape of natural aggregates; 2. Use carbonized steel slag artificial aggregate as the coarse and fine aggregate of the asphalt mixture, use a mixture of carbonized steel slag powder with the same particle size as basalt mineral powder and basalt mineral powder in a volume ratio of 1:1 as the filler of the asphalt mixture, add asphalt and fiber, and prepare an ultra-thin wearing layer asphalt mixture.
4. The method for preparing asphalt mixture of ultra-thin asphalt wearing layer by using full-size steel slag gradient carbonized artificial aggregate according to claim 3 is characterized in that: The mass of asphalt in asphalt mixture is 4 to 6% of the mass of asphalt mixture.
5. The method for preparing asphalt mixture of ultra-thin asphalt wearing layer by using full-size steel slag gradient carbonized artificial aggregate according to claim 3, characterized in that: The fiber in the asphalt mixture is steel slag fiber, and the mass of the steel slag fiber accounts for 0.2-0.4% of the mass of the asphalt mixture.
6. The method for preparing asphalt mixture of ultra-thin asphalt wearing layer by using full-size steel slag gradient carbonized artificial aggregate according to claim 3, characterized in that: The gradation of the ultra-thin wearing layer asphalt mixture is SMA-10, OGFC-10 or AC-10 asphalt mixture.
Citation Information
Patent Citations
Hydrated and carbonized composite hardened cementing material based on steel slag and preparation method of hydrated and carbonized composite hardened cementing material
CN114538806A
All-solid-waste artificial lightweight aggregate based on CO2 mineralization utilization and preparation method of all-solid-waste artificial lightweight aggregate
CN117510113A
Carbonization method for seel making slag
JP2014234332A
Cited By
Gradient carbonization-silane coupling synergistically modified steel slag and ultrathin wearing layer preparation method
CN120271259A
A preparation method of gradient carbonization-silane coupling synergistically modified steel slag and ultra-thin wearing layer
CN120271259B
Preparation method of carbon sequestration steel slag aggregate for asphalt pavement
CN121426448A